Zeolitic imidazolate framework-8: a versatile nanoplatform for tissue regeneration - Li, Zhixin; Shao, Yinjin; Yang, Youwen; Zan, Jun (Frontiers in Bioengineering and Biotechnology, 2024)
Extensive research on zeolitic imidazolate framework (ZIF-8) and its derivatives has highlighted their unique properties in nanomedicine. ZIF-8 exhibits advantages such as pH-responsive dissolution, easy surface functionalization, and efficient drug loading, making it an ideal nanosystem for intelligent drug delivery and phototherapy. These characteristics have sparked significant interest in its potential applications in tissue regeneration, particularly in bone, skin, and nerve regeneration. This review provides a comprehensive assessment of ZIF-8’s feasibility in tissue engineering, encompassing material synthesis, performance testing, and the development of multifunctional nanosystems. Furthermore, the latest advancements in the field, as well as potential limitations and future prospects, are discussed. Overall, this review emphasizes the latest developments in ZIF-8 in tissue engineering and highlights the potential of its multifunctional nanoplatforms for effective complex tissue repair.